Putting on the Mind of Ælred: Reflections of a Translator - Mayeski, Marie Anne (Cistercian studies quarterly, 2012)
The article focuses on the English translation of the sermons 29-46 for the Cistercian Fathers Series of Ælredi of Rievaulx. It notes that Ælrid has been giving details the way wherein worldly desires show themselves in vanity, sensuality, and ambition. It mentions that Ælrid discusses the logical distinction which develop into a more philosophical reflection on the origin of the soul in Sermon 34.